The Analysis of Identification and Risk Mitigation in Irrigation Work Contractors - Armandoko, Achmad Zulfikar; Ruzardi, Ruzardi; Musyafa, Albani (Jurnal Teknik Sipil dan Perencanaan, 2023)
Irrigation construction project work is a type of project that has a relatively high risk potential compared to other project work. The development of construction projects in Indonesia can be seen from the use of new methods and technologies as well as the increasing number of parties involved. Rehabilitation of the Progomanggis irrigation network is more complicated than other rehabilitation works because it covers a large area and is located in a place with difficult access. Therefore, this work is vulnerable to the risks that will arise. Based on the results of the analysis carried out, it can be concluded that the schedule for opening and closing river water in the Progomanggis Irrigation Network Rehabilitation Project has a very high risk of project performance. The impact of risk on the project is the delay in work time. Other risks are: weather conditions; changes in work methods; shunt materials; and cropping patterns of water-using communities. Risk control on the project is carried out by conducting regular coordination meetings with stakeholders and making adjustments to work methods.